Adaptation and validation of a test of ethical sensitivity in teaching. Issue 3 (3rd July 2021) - Maxwell, Bruce; Boon, Helen; Tanchuk, Nicolas; Rauwerda, Bryan
ABSTRACT: This article documents the adaptation, piloting and validation of a measure of teachers' ethical sensitivity. To create the test, we modified a measure from dentistry drawing on literature in teacher professional ethics and drew on the expertise of professional ethics scholars and practitioners. Based on the results of Rasch analysis combined with traditional approaches to psychometric validation, the instrument was found to be a valid and reliable means of discerning levels of ethical sensitivity within the group of participants. However, participants' lack of ethical sensitivity as revealed by overall low scores, we contend, lends credence to concerns that teacher education programs may not be adequately preparing future teachers to meet expectations in connection with the ethical dimensions of the profession. In conclusion, we call for further research on pre- and in-service teachers' capacity to perceive, reason about and react appropriately to ethical situations encountered at work.